Intestinal Fibrosis and Gut Microbiota: Clues From Other Organs - Zhan, Shukai; Li, Na; Liu, Caiguang; Mao, Ren; Wu, Dongxuan; Li, Tong; Chen, Minhu; Zhuang, Xiaojun; Zeng, Zhirong (Frontiers in Microbiology, 2021)
Fibrosis is a complex and difficult to elucidate pathological process with no available therapies. Growing evidence implicates intestinal microbiota in the occurrence and development of fibrosis, and the potential mechanisms involved in different organs have been explored in several studies. In this review, we summarize the causative and preventive effects of gut microbiota on intestinal fibrosis, as well as the relationships between gut microbiota and fibrosis in other organs. Interestingly, several colonized microbes are associated with fibrosis via their structural components and metabolic products. They may also play essential roles in regulating inflammation and fibroblast activation or differentiation, which modulates extracellular matrix formation. While the relationships between intestinal fibrosis and gut microbiota remain unclear, lessons can be drawn from the effects of gut microbiota on hepatic, cardiac, nephritic, and pulmonary fibrosis. Various intestinal microbes alterations have been detected in different fibrotic organs; however, the results were heterogeneous. Mechanisms by which the intestinal microbiota regulate fibrotic process in other organs, such as novel metabolic products or specific microbes, are also discussed. The specific microbiota associated with fibrosis in other organs could instruct future studies aiming to discover prospective mechanisms regulating intestinal fibrosis.